Academic Quorum Magazine Specialized in Communication and Information Issues University of Zulia - Publicación TELOS (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2004)
Academic Quorum Magazine Specialized in Communication and Information Issues University of Zulia